Effects of forest plantations on soil carbon sequestration and farmers’ livelihoods - Poultouchidou, Anatoli (2012)
The establishment of monoculture forest plantations with exotic, fast-growing species is common in tropical countries. This study was conducted to determine both (1) the long-term effects of plantations on soil organic carbon (SOC) and (2) the social impact of the plantation on farmers’ livelihoods in Ethiopia. Tree plantations of Cupressus lusitanica and Eucalyptus saligna were established on abandoned mechanized farmland nearly 30 years ago. SOC amounts under forest plantations were compared with SOC of mechanized farmland, traditional farmland and natural forest which was the reference site. The study had a retrospective design and differences in SOC contents were compared between the five land uses sampled at two different occasions with a 10-year interval. Moreover, 20 farmers in total, both male and female, living at different distances from the plantations, were interviewed in order to assess the difference in the social impact of the plantations on farmers’ livelihoods.